Ambient Assisted Living and Personal Health Records – Requirements and Challenges - Savoska, Snezana; Ristevski, Blagoj; Trajkovikj, Vladimir (My University, 2022)
We face enormous medical and health services demands due to the Covid-19 pandemic. This fact implies that the healthcare sector does not manage to cope with the considerable pressure from patients who experienced Covid-19, from which some fail to survive. The hospitals and medical practitioners everywhere were faced with significant stresses, and they were unable to cope with these problems. The patients were scared and unsatisfied with medical help, and the healthcare staff was exhausted everywhere. One of the solutions was implementing the concept of e-health with the usage of e-PHR of the patient and using some components of ambient assisted living (AAL), telemedicine, and telehealth. Many sensors for measuring vital signs of life are available on the market. Some applications can collect these data from IoT devices (sensors), wearables, or other devices that can help monitor the patient’s healthcare condition in a pandemic situation. In this way, healthcare professionals can access patients’ vital conditions and take actions such as e-prescription and e-referral. In the paper, we highlighted some aspects of possible healthcare improvement for the patients using AAL devices who can assist in improving access to medical and healthcare professionals, especially for the patients with chronic diseases, some disabilities, the elderly and children. This concept is based on the e-PHR concept, which understands that the patient owns their data and can access their e-Personal Health Record.
Keywords: Ambient Assisted Living, e-PHR, telemedicine, telehealth, e-health